2020
DOI: 10.1108/ecam-05-2020-0330
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of a wearable insole pressure system for measuring gait parameters to identify safety hazards in construction

Abstract: PurposeConstruction workers are frequently exposed to safety hazards on sites. Wearable sensing systems (e.g. wearable inertial measurement units (WIMUs), wearable insole pressure system (WIPS)) have been used to collect workers' gait patterns for distinguishing safety hazards. However, the performance of measuring WIPS-based gait parameters for identifying safety hazards as compared to a reference system (i.e. WIMUs) has not been studied. Therefore, this study examined the validity and reliability of measurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Current results are coherent with other studies examining the test and retest reliability of insole-based sensors [8][9][10][11][12][14][15][16]23,28,29]. However, the differences in the specific type of sensors used [16,30] and methodological limitations such as various spatiotemporal gait variables [13,28], several motor tasks [27,30] or the use of non-typical populations, do not allow direct comparisons of the results.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Current results are coherent with other studies examining the test and retest reliability of insole-based sensors [8][9][10][11][12][14][15][16]23,28,29]. However, the differences in the specific type of sensors used [16,30] and methodological limitations such as various spatiotemporal gait variables [13,28], several motor tasks [27,30] or the use of non-typical populations, do not allow direct comparisons of the results.…”
Section: Discussionsupporting
confidence: 73%
“…New low-cost devices have been developed to fill the gap in this sector [23]. However, the study of their validity and accuracy is still ongoing [2,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advancements and feasibility of wearable sensors (e.g., photoplethysmography, insole sensors, etc.) in the construction industry have made possible a real-time monitoring of biomechanical and physiological data to measure gait parameters, dynamic balance, and physical exertion without interfering worker's daily activities (Edirisinghe, 2019, Antwi-Afari et al, 2020b, Antwi-Afari et al, 2019, Kazar and Comu, 2021, Anwer et al, 2021a. For example, Antwi-Afari et al (2020b) indicated an excellent test-retest reliability (Intraclass correlation coefficient = 0.91) and good validity (Intraclass correlation coefficient = 0.75) of a wearable insole pressure system to measure gait parameters in a laboratory setting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fifteen healthy students aged 18 years or older (Mean age, 31.5 ± 2.6 years) were recruited by convenient sampling. Novel commercially available wearable insoles with plantar pressure sensors (OpenGo system, Moticon SCIENCE Sensor, Insole, GmbH, Munich, Germany) as shown in Figure 1 were used to quantify the gait and dynamic parameters (Refai et al, 2018, Stöggl and Martiner, 2017, Antwi-Afari et al, 2020b. The smart insoles with different sizes can fit in any shoe.…”
Section: Participantsmentioning
confidence: 99%
“…Kim et al [4] study a modified version of an off -the -shelf wearable device while Sakhakarmi and Park [5] propose a wearable, tactile-sensing system as a means of communication. Finally Antwi-Afari et al [6] focus attention on insole, in order to analyze the performance of workers for reasons related to safety on site while Kim and Ho [7] on relationship between wearable technologies and privacy. This latest study also analyzes the social aspects related to these issues, highlighting how facilitating social interaction among users and keeping personal information securely are keys to success in the dissemination of these devices.…”
Section: Introductionmentioning
confidence: 99%